Imaging Mass Spectrometry: Enabling a New Age of Discovery in Biology and Medicine Through Molecular Microscopy - Caprioli, Richard M. (Journal of the American Society for Mass Spectrometry, 2015)
Imaging mass spectrometry (IMS) has become a valuable tool for the production of molecular maps in samples ranging from solid inorganic materials to biologicals such as cells and tissues. The unique features of IMS are its ability to map a wide variety of different types of molecules, its superb molecular specificity, and its potential for discovery since no target-specific reagents are needed. IMS has made significant contributions in biology and medicine and promises to be a next generation tool in anatomic pathology. Graphical Abstract ᅟ